2016
DOI: 10.1074/jbc.m116.736140
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Specific Recognition of RhoA by the Dual GTPase-activating Protein ARAP3

Abstract: ARAP3 (Arf-GAP with Rho-GAP domain, ANK repeat, and PH domain-containing protein 3) is unique for its dual specificity GAPs (GTPase-activating protein) activity for Arf6 (ADPribosylation factor 6) and RhoA (Ras homolog gene family member A) regulated by phosphatidylinositol 3,4,5-trisphosphate and a small GTPase Rap1-GTP and is involved in regulation of cell shape and adhesion. However, the molecular interface between the ARAP3-RhoGAP domain and RhoA is unknown, as is the substrates specificity of the RhoGAP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…2A and S4A). We noticed that the region on CYK4 encompassing R385, L396, and P432 is located close to the GTPase residues that are distinct among RhoA, Cdc42, and Rac1 13,14 (Figs. 2A and S4B).…”
Section: To the Editormentioning
confidence: 96%
“…2A and S4A). We noticed that the region on CYK4 encompassing R385, L396, and P432 is located close to the GTPase residues that are distinct among RhoA, Cdc42, and Rac1 13,14 (Figs. 2A and S4B).…”
Section: To the Editormentioning
confidence: 96%
“…Thus, we investigated whether these new CDAIII variants might affect the GAP activity of CYK4 towards RhoA, Rac1, and Cdc42. GTP hydrolysis by RhoA, Rac1, or Cdc42 was monitored by measuring the released free phosphate using an enzyme coupled photometric assay under a multiple turnover condition in which the GDP release is not rate-limiting (26,27). The GAP activity was determined as the increase of the GTPase rate in the presence of the CYK4 GAP domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first criterion (i) was meant to provide a protein/peptide position agreeing with the deamidation reaction of Q63, whereas the second criterion (ii) was meant to obtain peptide conformations roughly fitting the folded structure of the G protein. The distance threshold for criterion (ii) was estimated from an analysis of the Cα-Cα distances between residues 60 and 72 in the RhoA structures corresponding to the following PDB entries: 1A2B [ 56 ], 1CC0 [ 57 ], 1CXZ [ 58 ], 1DPF [ 59 ], 1FTN [ 60 ], 1KMQ [ 61 ], 1LB1 [ 62 ], 1S1C [ 63 ], 1X86 [ 64 ], 1XCG [ 65 ], 2RGN [ 66 ], 3KZ1 [ 67 ], 3LW8 [ 68 ], 3LWN [ 68 ], 3LXR [ 68 ], 3MSX (to be published), 3T06 [ 69 ], 3TVD [ 70 ], 4D0N [ 71 ], 4F38 [ 72 ], 4XH9 [ 73 ], 4XOI [ 74 ], 4XSG [ 75 ], 4XSH [ 75 ], 5A0F [ 76 ], 5BWM [ 75 ], 5C2K (to be published), 5C4M (to be published), 5EZ6 (to be published), 5FR1 [ 77 ], 5FR2 [ 77 ], 5HPY [ 78 ], 5IRC [ 79 ], 5JCP [ 80 ], 5JHG (to be published), 5JHH (to be published), 6BC0 [ 81 ], 6BCA [ 68 ], and 6BCB [ 68 ]. This analysis revealed that the distances between the Cα atoms were in the range 9.4–10.8 Å.…”
Section: Methodsmentioning
confidence: 99%